The reaction of oleic acid monolayers with gas-phase ozone at the air water interface: the effect of sub-phase viscosity, and inert secondary components. Issue 48 (8th December 2020) - King, Martin D.; Jones, Stephanie H.; Lucas, Claire O. M.; Thompson, Katherine C.; Rennie, Adrian R.; Ward, Andrew D.; Marks, Amelia A.; Fisher, Fleur N.; Pfrang, Christian; Hughes, Arwel V.; Campbell, Richard A.
Abstract : Reaction of gas-phase ozone with oleic acid monolayer at the air–water interface leaves no product film. Reaction kinetics change with surface coverage but not with addition of unreactive material or with change of viscosity of the water. Abstract : Organic films that form on atmospheric particulate matter change the optical and cloud condensation nucleation properties of the particulate matter and consequently have implications for modern climate and climate models. The organic films are subject to attack from gas-phase oxidants present in ambient air. Here we revisit in greater detail the oxidation of a monolayer of oleic acid by gas-phase ozone at the air–water interface as this provides a model system for the oxidation reactions that occur at the air–water interface of aqueous atmospheric aerosol. Experiments were performed on monolayers of oleic acid at the air–liquid interface at atmospherically relevant ozone concentrations to investigate if the viscosity of the sub-phase influences the rate of the reaction and to determine the effect of the presence of a second component within the monolayer, stearic acid, which is generally considered to be non-reactive towards ozone, on the reaction kinetics as determined by neutron reflectometry measurements. Atmospheric aerosol can be extremely viscous. The kinetics of the reaction were found to be independent of the viscosity of the sub-phase below the monolayer over a range of moderate viscosities, , demonstrating no involvement of aqueous sub-phase oxidants in the rate determining step. The kinetics of oxidation of monolayers of pure oleic acid were found to depend on the surface coverage with different behaviour observed above and below a surface coverage of oleic acid of ∼1 × 10 18 molecule m −2 . Atmospheric aerosol are typically complex mixtures, and the presence of an additional compound in the monolayer that is inert to direct ozone oxidation, stearic acid, did not significantly change the reaction kinetics. It is demonstrated that oleic acid monolayers at the air–water interface do not leave any detectable material at the air–water interface, contradicting the previous work published in this journal which the authors now believe to be erroneous. The combined results presented here indicate that the kinetics, and thus the atmospheric chemical lifetime for unsaturated surface active materials at the air–water interface to loss by reaction with gas-phase ozone, can be considered to be independent of other materials present at either the air–water interface or in the aqueous sub-phase.